Evaluation of the Level of Services Provided to Persons with Disabilities in Jordan - AL-Momani, Mohammad Omar; Rababa, Elham Mahmoud (Journal of Posthumanism, 2025)
Objective: The study aimed to identify the level of general and specialized services related to persons with disabilities in Jordan. Material and Method: where the descriptive approach was used, in addition to using the questionnaire as a tool for the study. The questionnaire was applied to a sample consisting of (100) persons with disabilities and (300) parents of persons with disabilities, in order to find out the level of services provided to persons with disabilities. Results: and the results showed that the level of general and specialized services provided to such people in Jordan came up to a moderate degree, as a shortage appeared in some of these services. Conclusions: Expanding the care and rehabilitation services for people with disabilities in Jordan in quantity and quality to include remote areas and marginalized groups, as well as searching for people with disabilities who have not received services due to family ignorance or shame and organizing rehabilitative programs and services for people with disabilities and their guardians.